1990
DOI: 10.1524/ract.1990.49.4.155
|View full text |Cite
|
Sign up to set email alerts
|

Yields of Products from Thermal Neutron-Induced Fission of 235U

Abstract: A comprehensive study has been carried out of the yield pattern of fission products formed in thermal neutron-induced fission of 235 U. An isotope separator on-line a nuclear reactor was used for rapid separation of the fission products. At a target temperature of 2400 Q C all fission elements, with the exception of the little volatile transition elements zirconium, niobium, molybdenum, technetium, ruthenium, and rhodium, are released. Their isotopes are then available for study which means that a very complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…It is seen that most of the experimental yields follow Gaussian curve. There are, however, some notable exceptions, particularly in the data of RtrOSTAM et al 7 We believe that the data reported for 8tGe, 83Se and 133Te are probably cumulative yields. The values for tl6Ag, 12~ 127In are too high, whereas the values for 124In, 126In, 132Sb and 1361 are too low.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…It is seen that most of the experimental yields follow Gaussian curve. There are, however, some notable exceptions, particularly in the data of RtrOSTAM et al 7 We believe that the data reported for 8tGe, 83Se and 133Te are probably cumulative yields. The values for tl6Ag, 12~ 127In are too high, whereas the values for 124In, 126In, 132Sb and 1361 are too low.…”
Section: Resultsmentioning
confidence: 67%
“…We may indicate here that the isomer ratios for Table 1. Full circles are from Rt,'DSTAM et al 7 The squares are from the literature 6'12-18 and the triangles am from ERTm~. 8 The curve is the normal charge distribution curve from systematics Figure 1 shows the experimental fractional independent yields of isomers in the thermal neutron fission of 235U and the charge distribution curve from the Z v model of W~rtL.…”
Section: Resultsmentioning
confidence: 99%
“…It is called half-time for release in ref. 7 and represents the time necessary before half the amount produced at a certain moment has been released. The in case of di usion in an in nite foil 10.…”
Section: Results With the Molten U Targetmentioning
confidence: 99%
“…If we analyse our Cd data assuming e usion or desorption, then the release time is found to be 2 s, in quite good agreement with the results of ref. 7 , but in this case the quality of the t is poor. For iodine, the release time found in our experiment with the UC x target is much longer than the values obtained in the OSIRIS experiment.…”
Section: Discussionmentioning
confidence: 95%
“…The red line shows the yield of 86 Ge with the reference of 90rud1. The reference designated as 90rud1 is Radiochimica Acta 49, 155-191 (1990) [6]. However, the value of 0.87 ± 0.12 for 86 Ge is not found in the original paper.…”
Section: Fission Yields Of Jendl/fpymentioning
confidence: 99%